Is there fiscal space for financing an Arab development transformation? - Rathin Roy; Khalid Abu-Ismail; Raquel Almeida Ramos (International Policy Centre for Inclusive Growth (IPC-IG), 2012)
[Introduction] The fundamental development challenge in the Arab region is one of economic transformation or, more pertinent, a lack thereof. Heavy sectoral weights of extractive industries lead to dependence on global oil prices, even in oil-producing countries. The structure of production limits employment generation for skilled and semi-skilled labour. Low-skill services and informal activities then absorb the labour force, with corresponding harm to aggregate productivity and living standards. The slow emergence of manufacturing capacities distinguishes the economies of the Arab region from other developing countries. Compared to suitable aggregates or, more poignant, the successful Asian emerging economies, manufacturing exports from the Arab region do not contribute sufficiently to growth. Concurrently, growth is volatile and saving and investment rates are significantly below what is required to undertake this economic transition (see Arnim et al., 2011; Abu-Ismail, Moustafa, and Arabaci, 2011; Abu-Ismail et al., 2011). Certainly, counter-cyclical measures can support macroeconomic stability even in the face of commodity export dependence. However, several Arab countries have implemented such measures only recently through the creation of oil-stabilization funds. Structural retardation rather than structural transformation can thus characterize the analysis of macroeconomics of the Arab region. `Dutch disease' - the negative relationship between the relative size of extractive resource industries and overall GDP growth - appears to affect the oil-producing regions. Further, exploitation of natural resources crowds out investment and policy interest in developing manufacturing and high-value-added services, harming productivity and employment. Oil resources have thus largely retarded structural transformation for most of the Arab region (Arnim et al., 2011). The task is to reverse this retardation. This paper therefore approaches fiscal space by asking: What barriers to the creation and use of such fiscal space must be removed in order to undertake such a transformation? In posing this question, the paper seeks to clearly demarcate its treatment of the fiscal space issue from that of the fiscal fundamentalist: its concern is to ensure that fiscal space is created not in the abstract for an unspecified purpose. The purpose matters and, hence, judging the feasibility of creating and using fiscal space depends on the purpose for which the space is to be used. The rest of the paper details concrete policy options for undertaking the required structural transformation across the region. This transformation will doubtlessly require public resources. However, the resources will bring returns beyond the traditional growth dividend - first, in expanding the fiscal base; second, in fostering changes in the sources of revenue that will occur as the transformation takes effect; and third, in improving the equity and progressivity of the incidence of the fiscal burden and of public spending compared to the present situation. The discussion of fiscal space in this paper needs to be centred in this context.
Keywords: 330; Finanzpolitik; Nachhaltigkeit; Entwicklung; Systemtransformation; Arabische Staaten